Tindak Tutur Direktif dalam Video Belajar untuk Bayi dan Balita dalam Platform Youtube Kinderflix - Mustofa Zaen Zakcy; Shinta Nabila Az-Zahra; Sinta Maharani; Arizka Nurul; Bagus Muhammad Aunillah; Dzaka Abiyyu Mas’ud; Asep Purwo Yudi Utomo (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
Language serves as the most effective means of communication in everyday life, including within the context of early childhood education. One of the linguistic fields that examines language use is pragmatics, and one of its key focuses is directive speech acts, which function to guide interlocutors in performing specific actions. This study aims to describe the forms of directive speech acts found on the YouTube platform Kinderflix, which features educational videos for early childhood learners. This research employs a qualitative descriptive method, with data collected through observation and note-taking techniques, and analyzed using the distributional method. The findings reveal three types of directive speech acts, namely questions, commands, and requests. The results contribute to enriching the study of pragmatics, particularly in the area of directive speech acts. Furthermore, this research is expected to serve as a reference for content creators to pay closer attention to linguistic aspects in producing educational materials for early childhood. It is also hoped that this study can be further developed and serve as a useful foundation for future research.